Influencing factors for autism spectrum disorder in Chinese children: a meta analysis - CHEN Xi, YANG Hongsheng, LI Wei, ZHAI Rui, JIANG Yanlin, WANG Junhong (预防医学)
Objective: To systematically evaluate the influencing factors for autism spectrum disorder (ASD) in Chinese children, so as to provide the evidence for risk prediction and intervention of ASD. Methods: The publications pertaining to the influencing factors for ASD in Chinese children were retrieved from CNKI, Wanfang Data, VIP, PubMed and Embase database from inception to August 2024. A meta-analysis was performed using R package version 4.4.1. Sensitivity analysis was performed using the "leave-one-out" evaluation procedure. Publication bias was assessed using Egger regression test. Results: A total of 38 high-quality articles out of 9 015 articles were finally included, covering 149 607 individuals, with 5 974 cases of ASD. The meta-analysis showed that demographic factors including family history of related diseases (OR=14.958), maternal age of ≥35 years (OR=2.287) and parental history of hazardous occupations (OR=3.511); pregnancy-related factors including history of abortion (OR=5.832), no folate supplementation before and during pregnancy (OR=4.566), tobacco exposure before and during pregnancy (OR=2.596), history of other adverse exposures before and during pregnancy (OR=3.533), history of infectious diseases during pregnancy (OR=3.753), history of non-infectious diseases during pregnancy (OR=2.563), psychological problems during pregnancy (OR=3.864), history of medication during pregnancy (OR=6.651), adverse environmental exposures during pregnancy (OR=3.754), severe pregnancy reactions (OR=5.082), abnormal perinatal period (OR=2.987), cesarean delivery (OR=1.659), other perinatal adverse factors (OR=3.856), history of neonatal asphyxia (OR=2.792) and neonatal jaundice (OR=3.687); parenting factors including non-exclusive breastfeeding (OR=2.510), early/excessive screen exposure (OR=3.589) and feeding problems (OR=3.113); and individual factors including being male (OR=3.333) and history of convulsions/epilepsy (OR=7.035) were influencing factors for ASD in Chinese children. Conclusion: The prevalence of ASD in Chinese children is primarily associated with 23 influencing factors, including family history of related diseases, history of abortion, no folate supplementation before and during pregnancy, medication during pregnancy, early/excessive screen exposure and history of convulsions/epilepsy.